Rapid activation of peroxymonosulfate with iron(Ⅲ) complex for organic pollutants degradation via a non-radical pathway. (15th April 2023) - Wu, Shouying; Wu, Wei; Fan, Jianing; Zhang, Linping; Zhong, Yi; Xu, Hong; Mao, Zhiping
Highlights: A system was constructed to degrade organic pollutants by activating PMS with FeL. Mechanistic studies proved that FeL/PMS degrade RR195 via a non-radical pathway. The FeL/PMS system exhibits strong resistance to anions and humic acid. The FeL/PMS system could degrade RR195 effectively in the wide pH range of 4–10. A wide range of organic pollutants could be degraded by the FeL/PMS system. Abstract: Developing high-performance catalytic systems for eliminating contaminants effectively in water has received a lot of attention. However, the complexity of practical wastewater poses a challenge for degrading organic pollutants. Non-radical active species with strong resistance to interference have shown great advantages in degrading organic pollutants under complex aqueous conditions. Herein, a novel system was constructed by Fe(dpa)Cl2 (FeL, dpa =  N, N' -(4-nitro-1, 2-phenylene) dipicolinamide) activating peroxymonosulfate (PMS). The mechanism study verified that the FeL/PMS system had high efficiency in producing high-valent iron-oxo and singlet oxygen ( 1 O2 ) to degrade various organic pollutants. In addition, the chemical bonding between PMS and FeL was elucidated by the density functional theory (DFT) calculations. The FeL/PMS system could remove 96% Reactive Red 195 (RR195) in 2 min, which was much higher than other systems involved in this study. More attractively, the FeL/PMS system demonstrated general resistance to interference from common anions (Cl −, HCO3 −, NO3 − and SO4 2− ), humic acid (HA) and pH changes and were thus compatible with various natural waters. This work provides a new approach for producing non-radical active species, which is a promising catalytic system for water treatment. Graphical abstract: Image, graphical abstract